PERANCANGAN MASKOT ISI PADANGPANJANG SEBAGAI MEDIA BRANDING - Olvyanda Ariesta (Jurnal Bahasa Rupa, 2020)
Branding activities carried out to provide an image to the public about a brand. As one of the tertiary institutions in Sumatra that specializes in arts education, the Indonesian Institute of Art (ISI) Padangpanjang does not have a brand identity that is able to reach the public effectively. This has caused a lack of relationship between the ISI Padangpanjang and the public. To build a strong institutional identity that easily touches the public emotionally, gives a feeling of being closer so as to foster public trust in the institution, a mascot of ISI Padangpanjang has been designed. In the process, branding theory, as well as analysis of the vision of ISI Padangpanjang became the foundation in creating a mascot design. The results obtained are the creation of a mascot representing the ISI Padangpanjang named Si Kuaw. The Si Kuaw mascot design method is carried out through the design stages: research, thumbnails, roughs, comprehensive, and ready to press. As a media branding, the Si Kuaw mascot has been applied to various media, such as: motion graphics, art exhibition posters, new student acceptance brochures, pins, and mascots in the form of dolls.